2013
DOI: 10.5811/westjem.2011.5.6706
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Handheld Point-of-Care Fingertip Lactate Measurement in the Emergency Department

Abstract: Introduction: Early recognition of elevated lactate levels in sepsis may hasten the detection of those patients eligible for aggressive resuscitation. Point-of-care (POC) testing is now increasingly available for use in the emergency department (ED). We examined the accuracy and time-saving effect of a handheld POC device for the measurement of fingertip and whole blood lactate as compared with reference laboratory testing in critically ill ED patients.Methods: A convenience sample of adult ED patients receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 17 publications
(13 reference statements)
1
39
0
Order By: Relevance
“…The test performance characteristics in these contexts have been well-described. [3][4][5][6][7][8][9][10][11][12][13] Hypoglycemia and anemia are common complications of malaria that require laboratory diagnosis, because clinical assessment is an unsatisfactory substitute. Furthermore, lactate level at admission is an important prognostic indicator in severe malaria.…”
mentioning
confidence: 99%
“…The test performance characteristics in these contexts have been well-described. [3][4][5][6][7][8][9][10][11][12][13] Hypoglycemia and anemia are common complications of malaria that require laboratory diagnosis, because clinical assessment is an unsatisfactory substitute. Furthermore, lactate level at admission is an important prognostic indicator in severe malaria.…”
mentioning
confidence: 99%
“…This Vol 8, No 3, 2017 study is in concordance with previously available data/ studies that handheld POC lactate devices may serve as an effective alternative method of evaluation of blood lactate levels. [10,[20][21][22][23][24] A study conducted by Singer et al [24] showed that not only was there a reduction in time to administration of intravenous fl uids and antibiotics with a handheld/bedside POC device for lactate measurement, but there was also a reduction in the overall admissions to intensive care units and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Early recognition of elevated lactate levels in sepsis may hasten identification of patients eligible for aggressive resuscitation. [10] There are numerous hindrances to the early detection of lactate levels in the ED due to prolonged ED waiting time, increased patient volume and delays due to limitations of traditional laboratory analysis [11] Test results may therefore take hours to return and must be actively sought out by the clinician. The gold standard for the determination of lactate is the laboratory goldstandard enzymatic colorimetric assay method.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations are on-going for biochip immunoassay platforms for biomarkers such as CRP and PCT (12). Blood lactate levels are another nonspecific sepsis marker and research suggests that a POC lactate device may highlight patients at risk of sepsis and requiring resuscitation (13,14).…”
Section: Novel Diagnosticsmentioning
confidence: 99%